PENGARUH ERNING PER SHARE, CURRENT RATIO, DAN INFLAS TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE - Havisa Rahmania (Universitas Mahendradatta Denpasar, 2023)
Share price is an important consideration when assessing shareholder welfare and can be used as an indicator of how well a company is performing. The higher the stock price, the higher the value of the company. Conversely, a low stock price means that the value of the company will also be low. Low shares can mean the company's performance is not optimal. The author chose this title because he was interested in the problems that exist in the company. the problem with the company is the decline in stock prices in 2020. the value of current debt and net income of food and beverage companies fluctuates. the purpose of this study was to analyze the effect of EPS, CR, and inflation on stock prices. There are 7 companies listed on the Indonesian stock exchange in this study. This type of research is associative. research instruments in the form of financial reports that are accessed directly through the IDX website. based on the results of the analysis there is the effect of EPE, CR and inflation simultaneously on stock prices seen from the calculated f value which is greater than f table. Partially, EPS has an effect on stock prices, as seen from the t-count value which is greater than the t-table value. while CR and Inflation have no effect on stock prices because the t-count value is smaller than the t-table value.